Galantamine inhibits β‐amyloid‐induced cytostatic autophagy in PC12 cells through decreasing ROS production - Jiang, Sheng (Cell Prolif, 2018)
OBJECTIVES: Alzheimer's disease (AD) is one of the most prevalent brain diseases among the elderly, majority of which is caused by abnormal deposition of amyloid beta‐peptide (Aβ). Galantamine, currently the first‐line drug in treatment of AD, has been shown to diminish Aβ‐induced neurotoxicity and exert favourable neuroprotective effects, but the detail mechanisms remain unclear. MATERIALS AND METHODS: Effects of galantamine on Aβ‐induced cytotoxicity were checked by MTT, clone formation and apoptosis assays. The protein variations and reactive oxygen species (ROS) production were measured by western blotting analysis and dichloro‐dihydro‐fluorescein diacetate assay, respectively. RESULTS: Galantamine reversed Aβ‐induced cell growth inhibition and apoptosis in neuron cells PC12. Aβ activated the entire autophagy flux and accumulation of autophagosomes, and the inhibition of autophagy decreased the protein level of cleaved‐caspase‐3 and Aβ‐induced cytotoxicity. Meanwhile, galantamine suppressed Aβ‐mediated autophagy flux and accumulation of autophagosomes. Moreover, Aβ upregulated ROS accumulation, while ROS scavengers N‐acetyl‐l‐cysteine impaired Aβ‐mediated autophagy. Further investigation showed that galantamine downregulated NOX4 expression to inhibit Aβ‐mediated ROS accumulation and autophagy. CONCLUSIONS: Galantamine inhibits Aβ‐induced cytostatic autophagy through decreasing ROS accumulation, providing new insights into deep understanding of AD progression and molecular basis of galantamine in neuroprotection.